PERAN GURU SEBAGAI MODEL INSPIRASI DAN MOTIVASI RAMAH BUDAYA UNTUK MEMBIMBING SISWA DASAR - Ulfa Madina Fitrayani; Khusumadewi, Ari; Al Habsy , Bakhrudin (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
The role of teachers in education in Indonesia is very crucial, not only as teachers but also as mentors, motivators, and inspirators for students. In the context of cultural diversity, teachers are required to understand and appreciate the cultural background of students. This study aims to explore the role of teachers as culturally friendly models of inspiration and motivation in guiding students in elementary schools. Qualitative methods are used to analyze the challenges faced by teachers, including cultural diversity in the classroom, lack of multicultural training, and support from parents. The results of the study indicate that teachers who are able to integrate cultural values ​​and create an inclusive learning environment can shape students' characters with integrity. In addition, strategies for developing cultural competence and adequate training are needed to improve the effectiveness of the teacher's role. Thus, teachers have the potential to create a conducive learning atmosphere and support the spirit of diversity among students.